2016
DOI: 10.3732/ajb.1600199
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling plasticity of serotiny, a key adaptive trait in a Mediterranean conifer

Abstract: Growth-limiting environments exacerbated the precocious release of seeds, contrary to the ecotypic trend found for the aerial cone bank, suggesting a counter-gradient plasticity. This plastic response is potentially maladaptive under a scenario of frequent wildfires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 75 publications
(127 reference statements)
2
25
0
Order By: Relevance
“…Serotiny, mother plant age and fire severity effects on Pinus pinaster germination by Martín-Sanz et al (2016) in P. halepensis. The fact that cones of the young mother plants in this study are all serotinous could be attributed to a strong selection of this hereditary trait induced by fire.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
See 1 more Smart Citation
“…Serotiny, mother plant age and fire severity effects on Pinus pinaster germination by Martín-Sanz et al (2016) in P. halepensis. The fact that cones of the young mother plants in this study are all serotinous could be attributed to a strong selection of this hereditary trait induced by fire.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…If fire frequency exceeds the minimum time for the pines to produce viable seeds, their persistence could be compromised. On the other hand, if the time between two consecutive fires on the same area greatly increases the serotiny could be lost due to maintenance costs (Martín-Sanz et al 2016), to climatic factors or both (Espelta et al 2011, Martín-Sanz et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, a large variability in the degree of serotiny has been observed among populations across geographical gradients revealing that serotiny may increase with stand density and from northern to southern populations (Moya et al, 2007(Moya et al, , 2008de las Heras et al, 2012). Recently, studies conducted in common garden experiments have demonstrated, after controlling for the effects of tree size, that serotiny has a genetic basis and it is lower in pines from harsh (dry and cold) sites compared with mild sites (Martín-Sanz et al, 2016), while is more abundant on post-fire stands than on stands established in fire-free conditions (Ne'eman et al, 2004).…”
Section: Flowering Fruiting and Seed Productionmentioning
confidence: 99%
“…The species has a very short juvenile phase (Thanos and Daskalakou, 2000; Climent et al, 2008; Espelta et al, 2008), and builds canopy seed banks (Daskalakou and Thanos, 1996) consisting of both serotinous and non-serotinous cones with anatomically-different scales (Moya et al, 2008), whose ratio is dependent on both environmental and ontogenetic factors (Martín-Sanz et al, 2016). During its life cycle, this species progressively modifies the microenvironment to which its offspring are exposed through pre-fire litter production and necromass retention in the crown, which in turn affect fire intensity and post-fire products (Schwilk and Ackerly, 2001).…”
Section: Introductionmentioning
confidence: 99%